Study on the Main Drive Structure of Large Diameter Cold Mill - Zhang Dayong (Jixie chuandong)
The common structure of the main drive of the large diameter cold mill and its force analysis,balance method and the crankshaft lubrication design method are introduced. And this method is applied in the production practice,a good result is achieved.